Analisis Pengaruh Penggunaan Media Pembelajaran Interaktif pada Anak Tunagrahita - Denanda Yustika Sari; Maria Ulfah; Destiana Rahayu; Avni Khanafiyah; Sofi Asiyah; Lailia Nur Baity; Firman Ade Purnomo; Hidayatu Munawaroh (Universitas Palan, 2025)
Children with intellectual disabilities have below-average intellectual abilities that can affect their cognitive and memory skills. These children require special learning strategies tailored to their needs. This study aims to review the literature on the impact of using interactive media in teaching children with intellectual disabilities, focusing on their motivation and learning outcomes. The study employs a qualitative approach using a literature review method, analyzing various sources that discuss the effectiveness of interactive media, such as visual, audio, audiovisual, and interactive tools, in enhancing motivation and understanding among children with intellectual disabilities. The findings indicate that the use of interactive learning media can make learning more concrete, engaging, and enjoyable, effectively increasing students' motivation and interest in learning. The application of interactive media, such as pictures, animations, and teaching aids, is also effective in improving cognitive skills and short-term memory, enabling children to recognize letters, numbers, and early reading skills.